Lymphocyte apheresis for chimeric antigen receptor T‐cell manufacturing in children and young adults with leukemia and neuroblastoma. Issue 6 (13th March 2018) - Ceppi, Francesco; Rivers, Julie; Annesley, Colleen; Pinto, Navin; Park, Julie R.; Lindgren, Catherine; Mgebroff, Stephanie; Linn, Naomi; Delaney, Meghan; Gardner, Rebecca A.
Abstract : BACKGROUND: The first step in the production of chimeric antigen receptor T cells is the collection of autologous T cells using apheresis technology. The procedure is technically challenging, because patients often have low leukocyte counts and are heavily pretreated with multiple lines of chemotherapy, marrow transplantation, and/or radiotherapy. Here, we report our experience of collecting T lymphocytes for chimeric antigen receptor T‐cell manufacturing in pediatric and young adult patients with leukemia, non‐Hodgkin lymphoma, or neuroblastoma. STUDY DESIGN AND METHODS: Apheresis procedures were performed on a COBE Spectra machine using the mononuclear cell program, with a collection target of 1 × 10 9 total mononuclear cells per kilogram. Data were collected regarding preapheresis and postapheresis blood counts, apheresis parameters, products, and adverse events. RESULTS: Ninety‐nine patients (ages 1.3‐25.7 years) and 102 apheresis events were available for analysis. Patients underwent apheresis at a variety of absolute lymphocyte cell counts, with a median absolute lymphocyte count of 944 cells/μL (range, 142‐6944 cells/μL). Twenty‐two patients (21.6%) had absolute lymphocyte counts less than 500 cells/μL. The mononuclear cell target was obtained in 100% of all apheresis harvests, and chimeric antigen receptor T‐cell production was possible from the majority of collections (94%). Mononuclear cell collection efficiency was 65.4%, and T‐lymphocyte collection efficiency was 83.4%. Ten patients (9.8%) presented with minor adverse events during the 102 apheresis procedures, with one exception of a severe allergy. CONCLUSIONS: Mononuclear cell apheresis for chimeric antigen receptor T‐cell therapy is well tolerated and safe, and it is possible to obtain an adequate quantity of CD3+ lymphocytes for chimeric antigen receptor T‐cell manufacturing in heavily pretreated patients who have low lymphocyte counts.